Government spending and the budget deficit - Peitchinis, Stephen G. (Journal of business ethics, 1990)
The business community of Canada manifests questionable moral and ethical standards in its criticism of government spending, since it itself bears considerable responsibility for the increase in government spending and budget deficits. The contradiction arises from the failure of the business community to recognize the liberalization of society at large and the associated social responsibility for the well-being of its citizens; a well-being manifested in income maintenance programmes, in access to education and training, in health care, and others. The failure to recognize such expectations is manifested in its failure to provide adequately for the retirement of its employees, for the health care of its employees, for laid-off and seperated employees, thereby shifting the burden to government. Further, it has failed to assume responsibility for the training and retraining of the workers it employs, including high-level workers trained specifically to its purposes in business schools. While expecting government to bear full financial responsibility for income maintenance, health, education and training, the business community makes every effort to deny government the revenues it needs to meet its obligations. The avoidance of tax payments stands high amongst business objectives, manifested in the employment of highly paid accountants and tax lawyers specifically for the purpose. Finally, in their criticism of government spending, business spokesmen deliberately fail to distinguish between consumption spending and capital investment spending, notwithstanding the significant contribution to the production infrastructure of the economy of government investment expenditures. If the capital expenditures were to be taken out of the government's budget, the deficit will decrease substantially.